Revealing the diversity of Fusarium micromycetes in agroecosystems of the North Caucasus plains for replenishing the State Collection of Phytopathogenic Microorganisms of the All-Russian Scientific Research Institute of a Phytopathology - N. S. Zhemchuzhina; M. I. Kiseleva; T. M. Kolomiets; I. B. Ablova; A. P. Glinushkin; S. A. Elizarova (Вавиловский журнал генетики и селекции)
In order to prevent crop yield losses from the most dangerous and economically important pathogenic organisms, it is necessary not only to monitor the virulence gene pool, but also to study the nature of pathogen variability and determine the potential for the emergence of new genes and races. This requires centralized collections of fungal cultures characterized by a set of stable strains to provide for phytopathological, immunological, breeding, genetic, toxicological, parasitological and other studies. The State Collection of Phytopathogenic Microorganisms of the ARSRIP is the State Depository of Phytopathogenic microorganisms that are non-pathogenic to humans or farmed animals. Currently, it has more than 4,500 accessions of plant pathogenic strains of fungi, oomycetes, bacteria, viruses, phytoplasmas, and the collection is updated annually. For this purpose, the study of the inter- and intraspecific genetic diversity of genus Fusarium was carried out in agricultural systems of the Krasnodar Territory. In 2020, the State Collection of Phytopathogenic Microorganisms was supplemented with 13 strains of Fusarium fungi isolated from tissues of winter wheat plants collected in several locations of the Krasnodar region. The complex of Fusarium fungi revealed on winter wheat usually included Fusarium oxysporum, F. culmorum, F. lolii, F. graminearum, F. fujikuroi, F. sporotrichioides, etc. The effect of the preceding crop on the frequency of Fusarium species isolated from winter wheat was observed. After series cloning of collected isolates, 21 strains of different fungal species characterized by stable morphology traits and known pathogenic and phytotoxic properties were selected for collection replenishment. Significant differences in pathogenic activity were revealed between fungi belonging to either the same or different species; the manifestation of this activity varied from the absence of any effect of spore suspensions on seedling development to a complete inhibition of their growth. The phytotoxic activity towards wheat seedlings varied from medium to high. Species possessing a high intensity of phytotoxic activities are the most dangerous for wheat, since they promote accumulation of dangerous phytotoxins in plant tissues.